THE EFFECT OF GAME-BASED ICE-BREAKING ACTIVITIES ON ENGLISH VOCABULARY MASTERY AMONG SEVENTH-GRADE STUDENTS - Ni Wayan Kristya Dewi; Luh Mila Trisna Dewi; Luh Putu Dewi Ariani (JR-ELT (Journal of Research in English Language Teaching), 2026)
Vocabulary mastery is one of the essential components of English learning, yet many junior high school students experience difficulties in acquiring and retaining English vocabulary due to limited engagement during classroom instruction. This study aimed to investigate the effect of game-based ice-breaking activities on the English vocabulary mastery of seventh-grade students at SMP Negeri Satu Atap 3 Kubutambahan. A pre-experimental study employing a one-group pretest-posttest design was conducted with 19 seventh-grade students selected through total sampling. The research instrument consisted of a vocabulary test administered before and after six treatment sessions incorporating game-based ice-breaking activities. The collected data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed Rank Test. The findings revealed that the students' mean score increased from 50.87 in the pretest to 86.25 in the posttest. The hypothesis testing showed a significance value of 0.001 (p < 0.05), indicating a statistically significant improvement in students' vocabulary mastery after the treatment. These findings suggest that game-based ice-breaking activities effectively enhance students' English vocabulary mastery by promoting active participation and meaningful vocabulary practice in the classroom. Therefore, this strategy may serve as an effective alternative for English teachers to create a more engaging and interactive learning environment.